A Platinum(II) Terpyridine Metallogel with an L‐Valine‐Modified Alkynyl Ligand: Interplay of Pt⋅⋅⋅Pt, π–π and Hydrogen‐Bonding Interactions. Issue 46 (2nd October 2013) - Po, Charlotte; Ke, Zhihai; Tam, Anthony Yiu‐Yan; Chow, Hak‐Fun; Yam, Vivian Wing‐Wah
Abstract A series of platinum(II) terpyridine complexes with L‐valine‐modified alkynyl ligands has been synthesized. A complex with an unsubstituted terpyridine and one valine unit on the alkynyl is shown to be capable of gel formation, which is in sharp contrast to the gelation properties of the corresponding organic counterparts. Upon sol–gel transition, a drastic color change from yellow to red is observed, which is indicative of the involvement of Pt⋅⋅⋅Pt interactions. Through the concentration‐ and temperature‐dependent UV/Vis absorption, emission, circular dichroism, and 1H NMR studies, the contribution of hydrogen bonding, Pt⋅⋅⋅Pt and π–π stacking interactions as driving forces for gelation have been established, and the importance of maintaining a delicate balance between different intermolecular forces has also been illustrated.